Analyzing the relationship between advertising and sales promotion with brand equity - Abdullah, Haim Hilman; Hanaysha, Jalal R. M.; Abd Ghani, Noor Hasmini (2017)
In today’s competitive business environment, customers are considered to be the source of brand success. Customers have numerous choices to form among alternative products, and they apply a high level of effect in the market with regard to several aspects such as quality, product size, services, and price. Hence, it is very important for manufacturers to meet customers’ needs in order to stay competitive. Advertising and sales promotion are considered as the main tools of marketing communication which is influential in attracting the attention of the customer and building brand equity. Advertising and sales promotions are highly effective in affecting consumer purchase decisions of a particular brand. The main purpose of this paper is to analyze the link between advertising and sales promotion with brand equity. It reviews the past studies on the above-mentioned variables and provides some clarification to the nature of relationship existing between them.